O23.4 Understanding Domestic Violence as a Predictor of Adverse Health Outcomes and Sexual Risk-Taking Among Men Who Have Sex with Men (MSM): A Systematic Review and Meta-Analysis. (13th July 2013) - Buller, A; Bacchus, L; Devries, K
Abstract : Between 15.4% and 51% of men who have sex with men (MSM) have experienced domestic violence (DV). The adverse health consequences of DV are well documented for women victims, but little is known about the association between DV and health outcomes for men who have sex with men. We aimed to establish if MSM exposed to DV had higher odds of experiencing adverse health outcomes or engaging in risk behaviours. In this systematic review and meta-analysis, we searched 13 electronic databases to identify primary research studies reporting the risk of adverse health outcomes or risk behaviours for MSM experiencing or perpetrating DV. Of 4, 653 identified, 17 were included in the review, of which 15 were cross-sectional and 2 cohort. The 17 studies described 16 datasets with 12, 778 participants, reporting 82 estimates. All studies were included in the meta-analysis. We found that exposure to DV increased the odds of substance use (1·68, 95% CI 1·44–1·92), being HIV positive (1·4, 95% CI 1·19–1·62) and depression (1·6, 95% CI 1·28–1·92). Pooled crude odds ratios of the risk of unprotected anal sex in MSM exposed to DV were (1·49, 95% CI 0·67–2·30) with high level of heterogeneity among estimates. We conclude that DV has adverse health consequences for MSM. Exposure to DV is a risk factor for substance use, depression and HIV status. The evidence for the association between DV and sexual risk behaviour such as unprotected anal sex is less robust. There is a lack of cohort studies which limits the possibility to establish the direction of these associations. Studies are absent from Europe and low and middle income countries.